2022
DOI: 10.3389/fcimb.2022.961974
|View full text |Cite
|
Sign up to set email alerts
|

Changes of gut microbiota in colorectal cancer patients with Pentatrichomonas hominis infection

Abstract: Pentatrichomonas hominis is a parasitic trichomonads protozoa that parasitizes in the colon and cecum of humans and other animals. Our previous studies have demonstrated that infection with P. hominis is associated with the incidence of colon cancer (37.93%). However, the mechanism by which P. hominis infections increase the incidence of colon cancer remains unclear. Previous studies have suggested that certain parasites promote colon cancer by regulating gut microbiota. This study aimed to elucidate whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…Ruminococcaceae UCG-010 has a significant positive correlation with Occludin, while Ruminococcaceae UCG-014 and Candidatus Saccharimonas show a negative correlation with pro-inflammatory cytokines, , among which Ruminococcaceae UCG-014 is also capable of degrading complex carbohydrates . Of note, Coriobacteriaceae UCG-002 , Butyricimonas , Parabacteroides , Ruminococcaceae UCG-010 , and Ruminococcaceae UCG-014 are known to produce SCFAs, primarily propionate and butyrate. , Moreover, the relative abundances of Enterococcus , Lachnospiraceae NK4A136 group , and Escherichia-Shigella were noticeably diminished by YS108R EPS treatment. Enterococcus , a well-studied pathogenic genus, impairs the intestinal epithelial barrier through disruption of TJ function, becoming a contributor to gut inflammation, and is heavily enriched in patients with intestinal diseases, such as CRC and CD .…”
Section: Discussionmentioning
confidence: 99%
“…Ruminococcaceae UCG-010 has a significant positive correlation with Occludin, while Ruminococcaceae UCG-014 and Candidatus Saccharimonas show a negative correlation with pro-inflammatory cytokines, , among which Ruminococcaceae UCG-014 is also capable of degrading complex carbohydrates . Of note, Coriobacteriaceae UCG-002 , Butyricimonas , Parabacteroides , Ruminococcaceae UCG-010 , and Ruminococcaceae UCG-014 are known to produce SCFAs, primarily propionate and butyrate. , Moreover, the relative abundances of Enterococcus , Lachnospiraceae NK4A136 group , and Escherichia-Shigella were noticeably diminished by YS108R EPS treatment. Enterococcus , a well-studied pathogenic genus, impairs the intestinal epithelial barrier through disruption of TJ function, becoming a contributor to gut inflammation, and is heavily enriched in patients with intestinal diseases, such as CRC and CD .…”
Section: Discussionmentioning
confidence: 99%
“…The Eubacterium coprostanoligenes group is an anaerobic Gram‐positive coccus that degrades cholesterol, with metabolites including acetic acid, formic acid, and succinic acid. Veillonella is a common Gram‐negative anaerobic micrococcus found in the mouth cavity and intestine, 21 which can utilize lactic acid to create propionate and acetic acid 22 . Wang et al found that Lactobacillus reuteri regulates type 3 innate lymphoid cells (ILC3s) in HCC through acetic acid 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Veillonella is a common Gram-negative anaerobic micrococcus found in the mouth cavity and intestine, 21 which can utilize lactic acid to create propionate and acetic acid. 22 Wang et al found…”
Section: Discussionmentioning
confidence: 99%
“…The changes in intestinal microbiota may be related to the curative effect of colon cancer therapy [51,52]. Therefore, 16S ribosomal RNA (rRNA) sequencing analysis was performed to investigate the change of intestinal microbiota after PCM plus Laser-induced treatment.…”
Section: The Comprehensive Landscape Of Gut Microbiotamentioning
confidence: 99%